Simulation of TOPSIS calculation in Discrepancy-Tat Twam Asi evaluation model - Divayana, Dewa Gede Hendra; Suyasa, P. Wayan Arta (Register: Jurnal Ilmiah Teknologi Sistem Informasi, 2021)
This research’s main objective was to provide information related to the simulation of each calculation stage of the TOPSIS method used in the Discrepancy-Tat Twam Asi evaluation model. The TOPSIS method is used to find dominant indicators in the Discrepancy-Tat Twam Asi evaluation model that determines the effectiveness of blended learning in ICT Vocational Schools. This research used a quantitative approach. The questionnaires were used as a data collection tool in this study. Questionnaires were distributed to 20 respondents (teachers and students at several ICT Vocational Schools in Bali, Indonesia) for initial data needs and distributed to fourexperts to obtain data on the TOPSIS calculation effectiveness results. The analysis technique in this research was carried out by comparing the percentage of effectiveness test results with the standards. The results of this research showed that the simulation of TOPSIS method calculation in the Discrepancy-Tat Twam Asi evaluation model had run more effectively, as indicated by score was 93.13%. The simulation results showed the dominant indicator that determines the effectiveness of the blended learning implementation was I-2 (the existence of academic community support).